IDENTIFIKASI POTENSI PARIWISATA BERBASIS ANALISIS SWOT DI PULAU MAKALEHI KABUPATEN SITARO - Lagarense, Bet El; Adrah, Merry; Katulung, Chrisye M. (Jurnal Ilmu Pariwisata, 2023)
Tourism It is the most important sector to make the largest contribution to improving conditions in Indonesia. With the development of the privatization of government and the potential of those in Indonesia it will require the responsibility and the role of the central and local governments to work together to preserve and preserve each tourist attraction in their locality to remain an option of tourist destination. The study focused on identifying potential tourism based analyses on the island of Makalehi district of Sitaro province of North Sulawesi. The study aims to identify and explain the potential for tourism on the island of Makalehi using swot seta analysis approaches to analyze swot's results on the island of Makalehi district of sitaro province of Sulawesi. The method used was a descriptive qualitative study, the necessary data analysis technique that was one of the methods used to evaluate the strengths, weaknesses, opportunities and threats that led to the discovery of data in the field such as interviews, observations, librarian study and documentation. The study shows that Makalehi district in Sitaro province of North Sulawesi is a potential in Makalehi island and much more to improve, the weaknesses of Makalehi island have hamstrunged every economic legionnaire even in tourism, but the chances of investors can increase any of the support facilities in tourism such as inns, Cafes and restaurants to reduce any existing threats from outside Makalehi island so that they can serve as the economic boosters of Sitaro district especially on Makalehi island.